The child in time [videorecording (DVD)] - Cumberbatch, Benedict, 1976-; Macdonald, Kelly, 1976-; Moore, Stephen Campbell; Reeves, Saskia; McEwan, Ian (PBS Distribution, 2018)
Three years after his daughter went missing, children's author Stephen Lewis struggles to find purpose in his life without her. His wife Julie has left him, and his best friends Charles and Thelman have retired to the countryside, battling demons of their own. With tenderness and insight, the movie explores a marriage devastated, the loss of childhood, the fluidity of time, grief, hope, and acceptance.